Shynthesis and characterization of wollastonite glassceramics prepared from cullet doped with samarium oxide - Almasri, Karima A Mohamed (2018)
Wollastonite (CaSiO3) based glass ceramics doped with various amounts of samarium oxide (Sm2O3) were prepared using a melt-quenching technique based on the empirical formula [(CaO)0.21(SLS)0.79]1-y(Sm2O3)y, y=(0,1,2,3,4,5) wt.%. The effect of different sintering temperatures on physical, optical and structural properties of wollastonite (CaSiO3) based glass-ceramics were investigated for its potential application as a building material. In this work, soda lime silica glass waste was utilized as a source of silicon. The chemical composition and physical properties of glass were characterized by using Energy Dispersive X-ray Fluorescence (XRF) and Archimedes principle. The Archimedes measurement results show that the density increased with the increase of sintering temperature and doping Sm2O3 concentration. The generation of CaSiO3, morphology, size and crystal phase with increasing the heat-treatment temperature was examined by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Fourier transform infrared reflection spectroscopy (FTIR). The average calculated crystal size gained from XRD was found to be in the range 60 nm. XRD results show that after the sintering at 700 °C, the sample still in the amorphous phase. The increasing of sintering temperature to 800 °C cause the nucleation of triclinic wollastonite (CaSiO3), through increasing the sintering temperature to 900 ⁰C, para wollastonite (β-CaSiO3) phase appeared, and the progression of sintering temperature above 1000 ⁰C improved almost of the positions and relative intensities of the crystalline peaks. The FESEM results show a uniform distribution of particles and the morphology of the wollastonite crystal is granular. FTIR results exhibited the structural evolution of wollastonite based glass ceramics. The appearance of CaO, SiO2, and Ca-O-Si bands disclosed from FTIR which showed the formation of CaSiO3 crystal phase. In addition to the calculation of the energy band gap which found to be increased from 3.96 eV to 4.1 eV with increasing sintering temperature, also increased from 4.1 eV to 4.9 eV with increasing of samarium oxide concentration.